Could HLA-DR B1*11 allele be a clue for predicting extra-pulmonary sarcoidosis? - Ozyilmaz, Ezgi; Goruroglu Ozturk, Ozlem; Yunsel, Dilek; Deniz, Ali; Hanta, Ismail; Kuleci, Sedat; Seydaoglu, Gulsah; Erken, Eren; Kocabas, Ali (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Background: Several HLA-DR alleles have been described as a potential risk factor for sarcoidosis between distinct ethnic groups however the relationship between HLA-DR alleles and extra-pulmonary sarcoidosis (EPS) is still scarce. Objectives: The aim of this prospective study is to investigate the relationship between extra-pulmonary involvement and HLA-DR genetic analysis in Turkish patients with sarcoidosis. Methods: In this study, we HLA-typed sarcoidosis patients with and without extra-pulmonary involvement, and compared with healthy control subjects. The presence of EPS was evaluated with previously defined standard criteria (ACCESS) and only patients with definite and probable involvement were accepted as positive. Sequence Specific Oligonucletide Probes method was used for typing of HLA-DRB1 alleles from DNA samples in both groups. Results: The frequency of HLA DRB1*15 allele was more frequent in patients with sarcoidosis than controls (% 20.4 vs % 9.6)(pcorr=0.017). According to multivariate analysis (MVA), the presence of HLA DRB1*15 was indicated as an independent risk factor for sarcoidosis (OR:2.37; 95% CI: 1.31-4.30, p=0.004). Extra-pulmonary involvement was present in 39 patients (42.9 %). When the patients with and without extra-pulmonary involvement compared, HLADRB1*11 allele was significantly higher in patients without extra-pulmonary sarcoidosis which may be concluded as a protective allele for systemic involvement (%30.8 vs. %15.4)(p<0.05). This result was also confirmed with the MVA (OR:0.35, %95 CI:0.15-0.84, p=0.018). Conclusions: We demonstrated a strong positive link between the haplotype HLA DRB1*15 and sarcoidosis in a Turkish Caucasian population and a potential protective effect of HLA DRB1*11 from extra-pulmonary involvement of disease.